Analysis Of The Implementation Of Csr Programs On Environmental Performance (Case Study: Bio-Manufacturing Companies) - Slamet Wahyudi; Vita Ratnasari (International Journal Labs, 2025)
Harmonious relations between companies and surrounding communities are the dream of every industry. In reality, however, industries often experience conflicts with surrounding communities. This is due to several factors, namely those related to employment and environmental impacts. A notable social conflict occurred in 2012 when approximately 64 local residents staged a demonstration. To mitigate such conflicts, the company has adopted a community engagement approach through its Corporate Social Responsibility (CSR) program. This study examines the alignment and implementation of CSR programs in relation to their impact on environmental performance at a bio-manufacturing company located in East Java, Indonesia. To date, the company's CSR programs have incorporated suggestions from the local community. Based on company data, the percentage of social CSR programs is highly dominant at 83.5%, consisting of charity, religious, and natural disaster relief initiatives. This study employs an explanatory quantitative approach to test existing theories or hypotheses, aiming to strengthen or add to previous research findings. While other studies only use the CSR disclosure variable, this study includes the type of CSR variable that influences CSR disclosure and several external influences on environmental performance. The sample size for this study is 300 respondents from the community surrounding the company. Data was collected through the distribution of questionnaires and analyzed using SEM-PLS software. The results of the study indicate that CSR disclosure, pro-environmental community actions, and environmental NGOs have a positive and significant effect on environmental performance. The suitability of CSR programs for the community is the main factor influencing the value of CSR disclosure satisfaction. This study shows that the appropriate CSR programs for companies are social CSR, health CSR, and environmental CSR.